Intermediate-term follow-up of laparoscopic pectopexy cases and their effects on sexual function and quality of life: a cross-sectional study - Erdem, Selami (São Paulo Medical Journal, 2022)
BACKGROUND: Apical prolapsus refers to downward displacement of the vaginal apex, uterus or cervix. Pelvic organ prolapse (POP) can significantly affect women’s daily activities and sexuality. OBJECTIVE: To investigate, at the mid-term follow-up after laparoscopic pectopexy surgery, whether this procedure improved the patients’ quality of life and sexual function. DESIGN AND SETTING: In this cross-sectional study, data on patients who underwent laparoscopic pectopexy in the Gazi Yasargil Education and Research Hospital were evaluated. METHODS: Thirty-five patients with symptomatic apical prolapse and POP quantification stage II and higher were included in this study. We used the Turkish version of the female sexual function index (FSFI) questionnaire to assess preoperative and postoperative sexual dysfunction, and the Turkish version of the Prolapse Quality of Life Questionnaire (P-QOL) to evaluate the severity of POP and its impact on quality of life. RESULTS: The mean age, parity and length of follow-up of the patients were 36.08 ± 9.04 years, 4.00 ± 1.86 and 28.88 ± 5.88 months, respectively. The most common complications were de novo rectocele in three patients (8.6%) and de novo cystocele in two patients (5.7%). All the FSFI and P-QOL scores were statistically significantly improved in the postoperative period (P < 0.001 for all scores of both FSFI and P-QOL). CONCLUSION: The quality of life and sexual function of the patients who underwent laparoscopic pectopexy were found to have become statistically improved at the midterm follow-up. Laparoscopic pectopexy was found to be a viable, effective and safe procedure.